Paradikma Hukum Perlindungan Konsumen Di Era Ekonomi Digital Indonesia - Joni Laksito; Rengga Kusuma Putra (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
Objective: to determine trends in consumer legal protection in the digital economy era from various industries in Indonesia based on article reviews. Method: secondary data in the form of articles that match the research objectives with a publication period of 2014-2023, obtained online from Emerald, Elsevier, and Google Scholar. The analysis was carried out using Systematic Literature Review (SLR), using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. Results: The data search obtained 341 articles, and those that met the inclusion criteria were 9 (nine) articles with publication years 2019–2023 , in the fields of e-commerce, fintech, and online transportation. Article on cases of transactions via e-commerce and online transportation using UUITE No. 19 of 2016, and UUPK no. 8 of 1999. This regulation has not been able to meet increasingly dynamic market conditions and very sharp competition in the business world, so it has not been able to provide legal certainty to consumers. Problems in the fintech P2P lending sector use the legal basis of POJK No. 77 of 2016 concerning Information Technology-Based Money Lending Services. Regarding this regulation, it is still subjective, so it cannot provide protection to customers. In fact, there are still many illegal fintech loans found, thus outside the responsibility and authority of the OJK. Novelty: trends obtained from previous research regarding consumer legal protection. Future Research Agenda: conducting a study on the future of law in the digital economy era regarding obstacles in harmonizing various regulations.